Relationship between social and personal variables, body image, and wellbeing at work of nutritionists (2014)
The objective of this study was to investigate wellbeing in a random sample of nutritionists, using body image, and social and personal variables as causal factors, in an exploratory, crosssectional study. Statistical treatments included descriptive analyses, t-tests, ANOVAs, and linear regressions. The 242 participants perceived themselves frequently in a wellbeing state at work (M=3.8); 25.6% of participants presented a mildly distorted body image, 14.5% a moderately distorted body image, and 7.5% a severely distorted body image. Social and personal variables, such as having children and the level of personal income, were associated with wellbeing. Body image had a significant negative impact of 3.2 % on wellbeing.